2019
DOI: 10.1021/acs.molpharmaceut.9b00274
|View full text |Cite
|
Sign up to set email alerts
|

Avapritinib: A Selective Inhibitor of KIT and PDGFRα that Reverses ABCB1 and ABCG2-Mediated Multidrug Resistance in Cancer Cell Lines

Abstract: The frequent occurrence of multidrug resistance (MDR) conferred by the overexpression of ATPbinding cassette (ABC) transporters ABCB1 and ABCG2 in cancer cells remains a therapeutic obstacle for scientists and clinicians. Consequently, developing or identifying modulators of ABCB1 and ABCG2 that are suitable for clinical practice is of great importance. Therefore, we have explored the drug repositioning approach to identify candidate modulators of ABCB1 and ABCG2 from tyrosine kinase inhibitors with known phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 101 publications
3
36
0
Order By: Relevance
“…ABCB1-mediated ATP hydrolysis was stimulated by erdafitinib in a concentration-dependent manner ( Figure 5), which is consistent with previous reports [29,33,46,56,57] where the ATPase activity of ABCB1 can be stimulated by the presence of a competitive inhibitor in the substrate-binding pocket of ABCB1. Together with the results of erdafitinib stimulating ABCB1 ATPase activity, the in silico docking analysis of erdafitinib binding to ABCB1 in the inward-open conformation ( Figure 6) supports the notion that erdafitinib interacts with several amino acid residues within the transmembrane domain of ABCB1 and attenuates the binding of another drug substrate by direct competition (Figure 7).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…ABCB1-mediated ATP hydrolysis was stimulated by erdafitinib in a concentration-dependent manner ( Figure 5), which is consistent with previous reports [29,33,46,56,57] where the ATPase activity of ABCB1 can be stimulated by the presence of a competitive inhibitor in the substrate-binding pocket of ABCB1. Together with the results of erdafitinib stimulating ABCB1 ATPase activity, the in silico docking analysis of erdafitinib binding to ABCB1 in the inward-open conformation ( Figure 6) supports the notion that erdafitinib interacts with several amino acid residues within the transmembrane domain of ABCB1 and attenuates the binding of another drug substrate by direct competition (Figure 7).…”
Section: Discussionsupporting
confidence: 92%
“…More significantly, results of erdafitinib inhibiting the drug efflux function of ABCB1 ( Figure 2 ) and improving the susceptibility of KB-V-1 cells to drug-induced apoptosis ( Figure 4 ) indicate that erdafitinib reverses ABCB1-mediated multidrug resistance by restoring the cytotoxicity of ABCB1 substrate anticancer drugs in these multidrug-resistant cancer cells. Moreover, ABCB1-mediated ATP hydrolysis was stimulated by erdafitinib in a concentration-dependent manner ( Figure 5 ), which is consistent with previous reports [ 29 , 33 , 46 , 56 , 57 ] where the ATPase activity of ABCB1 can be stimulated by the presence of a competitive inhibitor in the substrate-binding pocket of ABCB1. Together with the results of erdafitinib stimulating ABCB1 ATPase activity, the in silico docking analysis of erdafitinib binding to ABCB1 in the inward-open conformation ( Figure 6 ) supports the notion that erdafitinib interacts with several amino acid residues within the transmembrane domain of ABCB1 and attenuates the binding of another drug substrate by direct competition ( Figure 7 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, ATPase assay of ABCB1 was performed to test if erdafitinib could alter the ATPase activity of ABCB1. Our results showed that erdafitinib concentration-dependently activated the ABCB1-associated ATPase, consisting with previous studies (42,43). Some ABC transporter substrate drugs can act as competitive inhibitors that bind to a distinct substrate-binding site and inhibit the efflux of a particular class of substrates (44).…”
Section: Discussionsupporting
confidence: 89%
“…Another possibility is that some substrate inhibitors can interact with ABCG2 on sites other than the substrate-binding sites and cause conformational changes in the binding pocket which allosterically affect the transportation of some substrates (59). It should be noted that, although several ABCG2 inhibitors were identified as substrates through ATPase assay, overexpression of ABCG2 does not necessarily confer drug resistance to these inhibitors (49,54,(60)(61)(62). Hitherto, the detailed mechanism of this inhibitory effect remained inconclusive and desire further exploration.…”
Section: Discussionmentioning
confidence: 99%